Human Capital Policies: What they Can and Cannot Do for Productivity and Poverty Reduction in Latin America - Suzanne Duryea; Carmen Pagés-Serra (Inter-American Development Bank, Research Department, 2002)
Raising labor productivity is recognized as a critical factor for increasing economic growth and reducing poverty levels in Latin America. Low levels of education continue to be singled out as the main obstacle to higher productivity in the region. We examine the scope for education to lift labor incomes above poverty levels in Latin America and find that in many countries education, by itself, has a positive, but limited, potential to increase wages above a minimum level. In general, the prospects are dim because progress in raising average schooling levels has been slow even under the best historical scenarios. We also examine whether the apparent failure of education can be explained by low wage returns to schooling, and poor underlying conditions. We find that investments in education continue to have important payoffs but poor underlying conditions explain the modest prospect for the role of education in the short run. This leads us to consider what additional policies should be pursued in order to ensure higher productivity for workers in the region.
Keywords: 330; Bildungsinvestition; Bildungspolitik; Bildungsniveau; Arbeitsproduktivität; Armut; Lateinamerika